In-plane transport anisotropy in a Ba1−xKxFe2As2 iron-based superconductor. (12th September 2019) - Matusiak, Marcin; Wolf, Thomas
Abstract: We report the in-plane anisotropy of the transport phenomena for the strain-detwinned single crystals of hole-doped 122 iron-pnictide Ba1- x K x Fe2 As2 . We study two under-doped samples ( x  = 0.11 and 0.22) which exhibit the simultaneous structural/magnetic transition from the tetragonal, paramagnetic phase to the orthorhombic, spin density wave phase at T tr  = 123 K and 86 K, respectively. Data on the anisotropy of the Seebeck and Nernst coefficients as well as the electrical resistivity are compared to results of measurements of Ba(Fe1- x Co x )2 As2 and Ca(Fe1- x Co x )2 As2 from previous studies. We conclude that the low temperature transport phenomena in Ba1- x K x Fe2 As2, unlike ones in the electron-doped counterparts, are possibly determined by anisotropic properties of the Dirac fermions.